Comparative analysis of smart home management systems - Bąk, Patryk; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2024)
The article presents a comparative analysis of smart home management systems. The paper includes an analysis of the market, from which two systems were selected for detailed analysis. The choice was between the open source locally running Home Assistant system and the cloud-based Google Home solution. The detailed analysis includes a comparison of documentation, functionality, configurability, security, architecture and user feedback. In addition, two studies were conducted. The first addressed the response time of end devices to perform an action in the smart home management system. The second, on the other hand, addressed the time and number of steps required to configure devices with the systems.